Kajian tentang Perlakuan Bentuk Konfigurasi Elektroda terhadap Kinerja Sensor Konduktivitas Listrik Tanah Jenis Kapasitif - Octavianus, Wahyu; Wijaya, I Made Anom S.; Budisanjaya, I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 4 No 2 (2016): September, 2016)
The measurement of EC can be conducted in two ways, namely electromagnetic induction and direct contact. This study using capacitive direct contact. The aims of this study were to determine the relationship of configurations shape each other of electrode to the measurements performance, and to determine to treatment that has the best performance. The study was started by designing the electrodes then continued by functional test and performance test. The treatments used was electrodes shape of ring, hair and triangle, and electrodes configuration of each shape was 2, 4, 6 and 8. The electrode probe was inserting into the soil with the depth of 20 cm to get the frequency and at the same time soil sample was collected for analyzed in the laboratory to get the EC values. Based on those data the relationship of between soil frequency and EC were then analyzed. The results indicated that the best performance was hair shapes with 2 configuration. The equation of soil frequency and EC was EC = 0.080590 F(soil) - 4.48289 with R2 = 0.851, RMSE = 0.066, stability = 0.02 and respond time = 7.41 second.
Keywords: Electric conductivity (EC): Capacitive sensor: Parallel chip sensor electrode: soil frequency: Performance test